Preparation and evaluation of adipic dihydrazide cross-linked hyaluronic acid microspheres for cephalexin - B. Padmasri; R. Kalyani; V. Anilkumar; D. Prasanth; M. Indu (Journal of Applied Pharmaceutical Research, 2021)
Hyaluronic acid also called as Hyaluronan, Sodium Hyaluronate (SA), sodium salt form of Hyaluronic acid is a biodegradable, biocompatible, and viscoelastic linear polysaccharide of a wide molecular weight range (1000 to 10,000,000 Da). In this project, described a method for preparing HA microspheres at different pH conditions by adapting a non-toxic and aqueous based crosslinking chemistry for sustained drug delivery of drugs. The derivatization chemistry of HA utilizing adipic dihydrazide has been used to construct hydrogels, applied for microsphere preparation. ADH was coupled efficiently to carbodimide-activated glucoronic acid residues of hyluronans. These ADH modified hyaluronan can be loaded with drug molecules and then cross linked into hydrogel. The drug was present in the bulk of hydrogel droplets which are present in liquid paraffin are precipitated by IPA. Formulating HA microspheres with this method have several advantages. Preliminary studies were conducted to confirm the better ratio of HA and ADH to show maximum entrapment efficiency and drug release. Then microspheres were prepared at different pH conditions and formulations were subjected to evaluation of various parameters like percentage yield, particle size, drug entrapment efficiency, porosity and bulk density, surface morphology, in vitro drug release among which F2B was optimized as best formulation which showed 74.6% entrapment efficiency and above 90% of drug release in 12 hours indicating Hyaluronic acid microspheres can be used as good carriers for sustained drug delivery of drugs.